A novel treatment of talar neck fractures with significant bone voids using cervical spine allograft - Anthony Wing, DO; Tung Dao, DPM; Ryan Stone, DPM; Daniel Degenova, DO; Trent Davis, DO; Benjamin Taylor, MD (Foot & Ankle Surgery: Techniques, Reports & Cases, 2025)
Talar neck fractures are rare and challenging injuries often associated with severe complications, including malunion, nonunion, and osteonecrosis. This case report highlights a novel surgical approach for managing a severely comminuted and displaced talar neck fracture with a substantial medial bone void using a tricorticocancellous cervical spine allograft. A 19-year-old male presented with a Hawkins IIA talar neck fracture, successfully treated through dual incision primary osteosynthesis, grafting, and stable internal fixation. Postoperative outcomes revealed radiographic union by four months, near-normal function at 17 months, and no evidence of avascular necrosis or malunion. This is the first reported case using a cervical spine allograft to address acute bone voids in talar neck fractures, demonstrating its viability as an alternative to autograft, with excellent functional and radiographic outcomes. The findings underscore the importance of innovative grafting techniques for managing complex talar injuries.